Colorable PID-resistant carbon fiber photovoltaic module frame
By setting honeycomb layers and conical honeycomb grid structures inside the photovoltaic module frame, and utilizing the synergistic effect of water-absorbing resin and microcapsules, rapid self-repair and high insulation are achieved, solving the technical problem of photovoltaic module frames in resisting PID effect, and improving the module's resistance to moisture penetration and service life.
Patent Information
- Application Number
- CN202511264010.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-09-05
AI Technical Summary
Existing photovoltaic module frames cannot simultaneously meet the requirements of rapid self-healing, high insulation, and resistance to moisture penetration in terms of resisting PID effects, resulting in module power degradation.
The frame of the photovoltaic module is made of colorable anti-PID carbon fiber, with a hollow honeycomb layer inside. The honeycomb cells are filled with microcapsules and water-absorbing resin. The honeycomb cells are designed as a conical structure that is narrow at the front and wide at the back. When the water-absorbing resin gets wet, it expands to form a hydrogel, which squeezes the microcapsules to release the repair material. The repair material flows along the conical channel to the crack and oxidizes and solidifies to form a sealing layer.
It enables rapid self-healing of cracks, blocks moisture penetration paths, forms a high insulation barrier, extends the service life of the frame, adapts to diverse application scenarios, and ensures the long-term sealing integrity of the components.
Smart Images

Figure CN120915240A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of photovoltaic modules, in particular to a colorable anti-PID carbon fiber photovoltaic module frame. BACKGROUND
[0002] In recent years, the performance of the photovoltaic module frame as a key structural component for protecting the internal battery piece directly affects the potential-induced degradation resistance of the module. Although the traditional aluminum alloy frame has good mechanical strength, it has the problems of high density weight increase, electrochemical corrosion risk and non-coloring limitation, which is difficult to meet the demand of building integrated photovoltaic. More seriously, the conductivity of aluminum alloy will exacerbate the PID effect in a high humidity environment, resulting in a sharp decline in the power of the module.
[0003] Micro-cracks trigger a PID chain reaction, which is caused by outdoor thermal stress cycles, and water seeps along the cracks to form electrolyte channels, causing current leakage between the battery piece and the frame. The current leakage triggers ion migration, causing the passivation layer of the battery piece to fail, and the power of the module to drop sharply. Therefore, considering the self-repairing technology and combining the existing technology experiments, three ways are proposed. The first way is to use microbial mineralization microcapsules, which have a long repair cycle and contain conductive calcium ions, which can form a leakage channel. The second way is to use dicyclopentadiene microcapsules, which rely on catalysts and cannot be polymerized in a non-catalytic environment. The third way is to use epoxy resin microcapsules, which cure slowly at room temperature and are triggered at high temperatures, delaying repair and causing water to continue to penetrate, resulting in excessive wet current leakage.
[0004] The existing technology cannot simultaneously meet the three requirements of rapid self-repairing, high insulation and anti-wet penetration, resulting in poor PID effect solving effect. SUMMARY
[0005] This section aims to summarize some aspects of the embodiments of the present application and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of the specification to avoid obscuring the purpose of this section, abstract and title, and such simplifications or omissions cannot be used to limit the scope of the present application.
[0006] In view of the above problems of the existing colorable anti-PID carbon fiber photovoltaic module frame, the present application is proposed.
[0007] Therefore, the purpose of the present application is to provide a colorable anti-PID carbon fiber photovoltaic module frame, which aims to simultaneously meet the three requirements of rapid self-repairing, high insulation and anti-wet penetration.
[0008] To solve the above technical problems, the present application provides the following technical scheme: a colorable anti-PID carbon fiber photovoltaic module frame, comprising a frame body, wherein the frame body is internally provided with a hollow structure; A honeycomb layer plate is embedded in the hollow structure of the frame body, and the honeycomb layer plate is composed of a plurality of regular hexagonal honeycomb cell arrays; Microcapsules are filled in the honeycomb cells, and the microcapsules encapsulate the oxidizable and curable repair material; A water-absorbing resin is arranged in the honeycomb cells and located at the front end of the microcapsules; The honeycomb cells have a tapered structure with a narrow front end and a wide rear end, and are used for guiding the directional flow of the repair material to the crack area.
[0009] According to the technical scheme, the honeycomb layer plate is arranged in the frame body, the microcapsules and the water-absorbing resin are filled in each honeycomb cell, and the microcapsules encapsulate the oxidizable and curable repair material. The honeycomb cells have a tapered structure with a narrow front end and a wide rear end, and can guide the directional flow of the repair material to the damage site when the front end is close to the crack area of the inner wall of the frame. When the crack occurs and the water vapor penetrates, the water-absorbing resin expands to form a hydrogel when wet, and physically extrudes the microcapsules to break and release the repair material. The repair material flows along the tapered channel to the crack, and is oxidized and cured to form a dense sealing layer after contacting the air. The structure realizes triple protection: actively repairing the crack, blocking the moisture penetration path, and forming a high insulation barrier, thereby eliminating the physical basis of potential-induced degradation from the root.
[0010] As a preferred scheme of the colored anti-PID carbon fiber photovoltaic module frame, the frame body is a detachable structure, including an upper shell and a lower shell which are symmetrical to each other. The upper shell and the lower shell are sealed and bonded by sealing silica gel.
[0011] According to the technical scheme, the frame body is composed of the symmetrical upper shell and the lower shell, and the two are bonded by low-temperature curing sealing silica gel. The sealing silica gel fills the assembly gap and forms an elastic sealing layer, and has a low expansion rate after curing, effectively preventing external water vapor from entering. The split design allows the shell to be disassembled and replaced with the internal honeycomb layer plate, so that only partial replacement is required when the repair function is exhausted, instead of the whole being scrapped. When disassembled, the sealing silica gel is softened by heating, and the new honeycomb layer plate is embedded after peeling off and re-injection and curing. This design significantly prolongs the service life of the frame, and also meets the customized maintenance needs in different corrosive environments such as deserts and coasts.
[0012] As a preferred scheme of the colored anti-PID carbon fiber photovoltaic module frame, the frame body is a detachable structure, including an upper shell and a lower shell which are symmetrical to each other. Limiting grooves are respectively formed in the positioning blocks and the limiting blocks.
[0013] The technical scheme is adopted, the positioning block is fixed on the edge of the upper shell, the limiting block is correspondingly arranged on the lower shell, and the thicknesses of the two are consistent with the shell to form a continuous plane. The limiting groove is arranged in the positioning block and the limiting block, and the groove body is a groove structure with gradually changed depth. When assembled, the vertical alignment reference is established through the limiting groove, and it is ensured that the upper and lower shells are completely overlapped without misalignment. The mechanical positioning mode eliminates the manual alignment error, prevents the sealing silica gel from being cracked due to the misalignment of the shell, and maintains the long-term sealing integrity.
[0014] As a preferred scheme of the colorable anti-PID carbon fiber photovoltaic module frame, the limiting groove is a conical structure with a narrow upper part and a wide lower part. The locking member is movably inserted into the limiting groove, and is used for locking the vertical positions of the positioning block and the limiting block.
[0015] The technical scheme is adopted, the limiting groove is a conical structure with a narrow upper part and a wide lower part, and the inclination angle of the inner wall is matched with the outer contour of the locking member. The locking member can be inserted into the limiting groove, and when the bottom end of the locking member contacts the bottom conical surface of the groove, the outer wall of the locking member is in surface contact with the groove wall. The conical structure converts the axial pressure of the locking member into radial expansion force, so that the locking member is tightly attached to the groove wall. This design has three advantages: automatic guiding and correction of position deviation during insertion; increased contact area to improve shear strength; and self-locking effect generated by the conical surface to prevent loosening. This insertion type locking greatly simplifies the assembly process, and at the same time provides mechanical stability against vibration and impact.
[0016] As a preferred scheme of the colorable anti-PID carbon fiber photovoltaic module frame, the locking member comprises: A threaded handle is located at the top end of the locking member. A cast iron disc is arranged in the internal cavity of the locking member and is movably connected with the threaded rod of the threaded handle. A conical block is located below the cast iron disc. A compression spring is arranged between the cast iron disc and the conical block. A steel ball is arranged in a spherical groove on the surface of the locking member and is partially exposed by being extruded by the conical block.
[0017] The technical scheme is adopted, the threaded handle at the top is connected with the cast iron disc in the middle, and the conical block is arranged below the cast iron disc, and the two are connected through the compression spring. When the threaded handle is screwed, the cast iron disc is pushed downward, the compression spring is compressed, and the conical block is vertically moved. The steel ball is arranged between the outer wall of the conical block and the internal cavity of the locking member, and is half-embedded in the spherical groove. When the conical block is moved downward, the conical surface extrudes the steel ball to protrude radially outward from the locking member. This design converts the axial rotation force of manual screwing into radial mechanical expansion force, and realizes physical locking through the protrusion of the steel ball.
[0018] As a preferred scheme of the colorable anti-PID carbon fiber photovoltaic module frame, the outer surface of the conical block is inclined to the inclined end of the limiting groove bottom to form a right-angle wrap structure. The steel ball forms a lever force lock with the bottom of the limiting groove when the conical block is pressed.
[0019] The above technical scheme is adopted. When the steel ball is pressed by the conical block, part of the convex locking part protrudes from the surface and forms a point-surface contact with the inclined surface of the limiting groove bottom. When an external force attempts to separate the positioning block and the limiting block, the steel ball is subjected to a pressing force from the inclined surface of the limiting groove, which is transmitted along the center of the steel ball to the inclined surface of the conical block. Because the two inclined surfaces form a right-angle wrap structure, the reaction force is decomposed into a component force perpendicular to the movement direction of the conical block, so that the conical block is pressed more tightly. This lever effect makes the locking force increase with the increase of the external force, realizes complete mechanical self-locking, and completely avoids the risk of accidental unlocking in a vibrating environment.
[0020] As a preferred scheme of the colorable anti-PID carbon fiber photovoltaic module frame, the frame body is an integrally formed structure, and the internal hollow part is completely matched with the shape of the honeycomb layer plate.
[0021] The above technical scheme is adopted. The internal hollow structure of the frame body is completely matched with the shape of the honeycomb layer plate. After the honeycomb layer plate is embedded, it is tightly fitted with the inner wall of the frame without gaps, eliminating the assembly gaps of the split structure. The overall structure can resist high-pressure water penetration in a water immersion environment and avoid particle intrusion and friction damage in high-dust conditions. Although the replaceability is sacrificed, the repair life is compensated by increasing the microcapsule filling rate, which is particularly suitable for offshore power stations, desert power stations and other difficult-to-maintain extreme scenarios.
[0022] As a preferred scheme of the colorable anti-PID carbon fiber photovoltaic module frame, the water-absorbing resin is in the form of particles, which expands to form a hydrogel when exposed to water vapor, and the microcapsule is broken to release the repair material.
[0023] The above technical scheme is adopted. The water-absorbing resin is pre-installed in the form of particles in front of the microcapsule. When cracks allow moisture to penetrate the honeycomb cells, the resin particles absorb water and expand by hundreds of times. The expanded resin forms a hydrogel with a three-dimensional network structure, which does not release water when under pressure, but continuously fills the space in the honeycomb cells. The continuous expansion of the hydrogel generates uniform lateral pressure, gradually extruding the microcapsule until its wall material breaks. This physical trigger mechanism does not require electricity or heat source, and only relies on environmental humidity to automatically activate the repair function, achieving a truly passive intelligent response.
[0024] As a preferred scheme of the colorable anti-PID carbon fiber photovoltaic module frame, the wall material of the microcapsule is polyurethane, and the core material contains an oxidized curing type repair monomer and an initiator.
[0025] With the technical scheme, the microcapsule adopts polyurethane material as the wall material, the molecular chain of which contains urethane groups, which remain chemically inert in the alkaline environment of concrete, avoiding premature degradation of the repair material. The core material contains oxidized curing monomers and peroxide initiators, and the monomers initiate free radical chain reactions after contacting air, transforming from liquid to solid polymer. The curing product forms a cross-linked network structure, which not only blocks the cracks but also provides a light insulation layer with a volume resistivity exceeding the standard, double blocking the channels of electron migration and ion penetration.
[0026] As a preferred scheme of the colorable anti-PID carbon fiber photovoltaic module frame of the present application, wherein: the tapered front end of the honeycomb lattice faces the inner wall surface of the frame body, and the rear end faces the central axis of the honeycomb layer plate.
[0027] With the technical scheme, the honeycomb lattice has a tapered structure with a narrow front end facing the inner wall surface of the frame body and a wide rear end facing the central axis of the honeycomb layer plate. When the repair material is released from the broken microcapsule, it flows along the tapered space under the extrusion of the hydrogel. The geometry of the narrow front and wide rear creates a Venturi effect, accelerating the convergence of the repair material to the crack area of the inner wall of the frame. At the same time, the tapered channel blocks the reverse flow, ensuring that the repair material preferentially fills the cracks rather than flowing back to the interior of the honeycomb lattice. This design improves the repair efficiency and significantly improves the crack coverage completeness under the same amount.
[0028] Compared with the prior art, the present application has the following beneficial effects: The water-absorbing resin swells when wet, triggering the rupture of the microcapsule, and the released repair material flows directionally along the tapered honeycomb lattice to the crack area, forming a high-insulation sealing layer after oxidation and curing, completely blocking the moisture penetration path and eliminating the risk of potential-induced degradation. The detachable shell cooperates with the heat-softening sealant structure, supporting the convenient replacement of the honeycomb layer plate, and significantly extending the service life. The integrated structure improves the sealing reliability in harsh environments, adapts to various application scenarios, and the locking piece maintains stable locking force in a vibrating environment through the lever self-locking mechanism of the steel ball and the conical block, ensuring the long-term sealing integrity of the frame. The crack repair, moisture barrier, and high-insulation barrier work together to solve the industry problem of being unable to balance fast self-repair, high insulation, and moisture resistance in the prior art. BRIEF DESCRIPTION OF DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiment description. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can also be obtained by those skilled in the art without creative labor. Among them: Figure 1 It is the overall structure schematic diagram of embodiment 1 of the colorable anti-PID carbon fiber photovoltaic module frame of the present application.
[0030] Figure 2 The internal cross-section structure diagram of the frame body of the embodiment 2 of the colorable anti-PID carbon fiber photovoltaic module frame of the present application.
[0031] Figure 3 The internal cross-section structure diagram of the positioning block and the limiting block of the colorable anti-PID carbon fiber photovoltaic module frame of the present application.
[0032] Figure 4 The internal cross-section structure diagram of the locking piece of the colorable anti-PID carbon fiber photovoltaic module frame of the present application.
[0033] Figure 5 The disassembly and assembly structure diagram of the positioning block, the limiting block and the locking piece of the colorable anti-PID carbon fiber photovoltaic module frame of the present application.
[0034] Figure 6 The motion state diagram of the microcapsule and the water-absorbing resin of the colorable anti-PID carbon fiber photovoltaic module frame of the present application.
[0035] Figure 7 The sealing silicone filling state diagram of the colorable anti-PID carbon fiber photovoltaic module frame of the present application.
[0036] Figure 8 The honeycomb layer plate replacement process structure diagram of the colorable anti-PID carbon fiber photovoltaic module frame of the present application.
[0037] Figure 9 The microcapsule and water-absorbing resin filling state process structure diagram of the colorable anti-PID carbon fiber photovoltaic module frame of the present application.
[0038] Figure 10 The crack repair structure diagram of the microcapsule prepared in the comparative example 1 of the present application.
[0039] Figure 11 The crack repair structure diagram of the microcapsule prepared in the comparative example 2 of the present application.
[0040] Figure 12 The crack repair structure diagram of the microcapsule prepared in the embodiment 1 of the present application.
[0041] In the figure: 1, frame body; 2, upper shell; 3, lower shell; 4, honeycomb layer plate; 5, honeycomb cell; 6, microcapsule; 7, water-absorbing resin; 8, positioning block; 9, limiting block; 10, limiting groove; 11, locking piece; 12, threaded handle; 13, spherical groove; 14, steel ball; 15, cast iron disc; 16, conical block; 17, compression spring; 18, sealing silicone. DETAILED DESCRIPTION
[0042] In order to make the above objectives, features and advantages of the present application more obvious and comprehensible, the specific embodiments of the present application will be described in detail below with reference to the accompanying drawings.
[0043] In the following description, a large number of specific details are set forth in order to facilitate a thorough understanding of the present application, but the present application can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without departing from the concept of the present application, so the present application is not limited to the specific embodiments disclosed below.
[0044] Secondly, the "one embodiment" or "embodiment" referred to herein means that the specific features, structures or characteristics can be included in at least one implementation of the present application. "In one embodiment" appearing in different places in the specification does not mean the same embodiment, nor is it an embodiment that is separate or alternative to other embodiments.
[0045] Thirdly, the present application is described in detail in conjunction with the schematic diagram, and in the detailed description of the embodiments of the present application, the cross-sectional view of the device structure is partially enlarged without the general proportion for the convenience of description, and the schematic diagram is only an example, which should not limit the scope of protection of the present application herein. In addition, three-dimensional spatial dimensions including length, width and depth should be included in actual manufacture. Embodiment 1
[0046] Reference Figures 1-7 For the first embodiment of the present application, a colorable PID-resistant carbon fiber photovoltaic module frame is provided, and the device comprises: The frame body 1 is detachable and integrally formed, and in this embodiment, it is detachable. The frame body 1 is composed of an upper shell 2 and a lower shell 3. The upper shell 2 and the lower shell 3 are symmetrical, and the inside of the two is a hollow structure. The shape of the hollow part is matched with the shape of the honeycomb layer plate 4; The size of the honeycomb layer plate 4 is the total volume of the upper shell 2 and the lower shell 3. The outer surface of the honeycomb layer plate 4 is composed of a plurality of regular hexagonal honeycomb arrays. Each independent honeycomb cell 5 is provided with the same volume structure. The honeycomb cell 5 is provided with microcapsules 6 and water absorbing resin 7. The microcapsules 6 occupy 60% of the volume space of the honeycomb cell 5, and the diameter is 80±10μm to form a nested structure of the microcapsules 6. The microcapsules 6 are filled with triethylene glycol dimethacrylate. The material is a liquid filled in the crack, and is gradually solidified after oxidation, and finally forms a repair structure; The honeycomb cell 5 also contains microcapsules 6 containing chelating agents. The amount of the microcapsules 6 containing chelating agents is 1:50 of the amount of triethylene glycol dimethacrylate. The amount of chelating agents is small, and the honeycomb cell 5 is in a conical shape, which is narrow in front and wide at the back, as shown in the enlarged view. Figure 1 The enlarged view shows that the solvent can be guided to flow; The honeycomb 5 is also provided with water-absorbing resin 7, which is in a granular structure, and is pre-set in front of the microcapsule 6. When the surface of the frame body 1 is cracked, external water vapor penetrates between the honeycomb 5 and the frame body 1, and the water-absorbing resin 7 absorbs the water vapor and expands to hundreds of times its original volume. The water-absorbing resin 7 expands to form a hydrogel. Even if the hydrogel is pressed, it cannot separate the water due to its material properties. Therefore, the expanded hydrogel fills the inside of the honeycomb 5. Since the honeycomb 5 is filled, it exerts pressure on the microcapsule 6, which breaks. The triethylene glycol dimethacrylate inside the microcapsule 6 flows from the gap in the hydrogel to the gap in the frame body 1 and solidifies after oxidation. Therefore, the expansion of the water-absorbing resin generates uniform lateral pressure, pushing the microcapsule to move in the direction of the crack and break. Temperature conditions: System Temperature range Time Pure TEGDMA + BPO 60-80℃ 30-60 minutes TEGDMA + BPO + DMT 0.5% Room temperature - 40°C 5-15 minutes Curing time: Light intensity Curing time thickness 1 mm 500 mW / cm2 20-40 seconds 1000 mW / cm2 10-20 seconds Formulation ingredient ratio: Ingredients Proportion Role TEGDMA 30-50% Reduce viscosity, improve conversion rate Bis-GMA 50-70% Enhance mechanical strength Photoinitiator (TPO) 0.5-1.5% Initiate polymerization Silica 50-70 wt% Enhance wear resistance Preparation method of triethylene glycol dimethacrylate TEGDMA microcapsule: The raw materials are the capsule core and TEGDMA-90g and benzoyl peroxide 0.9g, the wall material is diphenyl methane diisocyanate 15g and ethylenediamine 10g, and the solvent is cyclohexane 200ml. The steps are as follows: S1, prepare TEGDMA and benzoyl peroxide by oil phase preparation, then add diphenyl methane diisocyanate 15g under nitrogen protection and stir for 30 minutes; S2, prepare ethylenediamine 10g and 0.5% PVA solution 300ML by water phase preparation method under 45 degrees Celsius environment; S3, use interface polymerization method again, stir the oil phase into the water phase under 1200rpm speed, then warm up the stirring environment to 60 degrees Celsius and react for 2 hours, finally form polyurethane wall material in situ; S4, finally perform filtration treatment, then wash with cyclohexane 3 times, vacuum dry at 35 degrees Celsius for not less than 12 hours, and sieve through a 75-105μm mesh sieve, finally get transparent spherical microcapsules.
[0047] The repair mechanism is that triethylene glycol dimethacrylate is rapidly cured at 40-80 degrees Celsius under the action of an oxidizing agent, with a curing time of 30-60 minutes. After the lipid expands and squeezes the microcapsule, the liquid monomer contacts air and solidifies to form a dense polymer to fill the crack.
[0048] The whole honeycomb layer plate 4 is composed of honeycomb cells 5, therefore, the honeycomb cells 5 are provided with the honeycomb cells 5 capable of repairing cracks on each bonding surface of the frame body 1, therefore, the whole frame body 1 can be fully covered; The connecting end between the upper shell 2 and the lower shell 3 is filled with sealing silica gel 18, before installation, the upper shell 2 and the lower shell 3 are filled with liquid sealing silica gel 18, the sealing silica gel 18 is cured at low temperature, the sealing silica gel 18 fills the assembly gap, the expansion rate after curing is 5%, therefore, the self-volume change is not large, water vapor is prevented from penetrating from the assembly gap, the detachable structure of the upper shell 2 and the lower shell 3 can adapt to various application scenarios, the honeycomb layer plate 4 inside is convenient to disassemble and assemble, when the honeycomb layer plate 4 needs to be replaced, the sealing silica gel 18 needs to be softened by high temperature, the temperature needs to be above 120 degrees Celsius, and the heating time needs to be between 15-20 minutes, after softening, the sealing silica gel 18 can be directly peeled off, and then the honeycomb layer plate 4 is embedded between the upper shell 2 and the lower shell 3, and then according to the situation, the sealing silica gel 18 raw material is added again and then cured; After the sealing treatment of the upper shell 2 and the lower shell 3, vertical limiting is still needed, the vertical limiting structure includes a positioning block 8 and a limiting block 9, the positioning block 8 and the limiting block 9 are respectively arranged outside the upper shell 2 and the lower shell 3 of the frame body 1, and the shapes of the positioning block 8 and the limiting block 9 are matched, and the thicknesses of the positioning block 8 and the limiting block 9 are the same as the thicknesses of the corresponding upper shell 2 and lower shell 3; The upper shell 2 and the lower shell 3 are respectively provided with a limiting groove 10, the limiting groove 10 is narrow at the top and wide at the bottom, the bottom of the limiting groove 10 is a conical structure, the conical structure is still narrow at the top and wide at the bottom, the inclined surface of the limiting groove 10 corresponds to the position of the spherical groove 13 of the locking piece 11, the spherical groove 13 is annularly distributed inside the locking piece 11, and the locking piece 11 is movably inserted into the limiting groove 10; When the bottom of the limiting groove 10 and one end of the locking piece 11 are attached, it means that the locking piece 11 is positioned successfully. The locking piece 11 includes a threaded handle 12, a spherical groove 13, a steel ball 14, a cast iron disc 15, a conical block 16 and a compression spring 17. The threaded handle 12 is located at the top end of the locking piece 11, and the bottom of the threaded handle 12 is a threaded rod and is threadedly connected with the locking piece 11. The cast iron disc 15 is circular and is pre-set in the internal cavity of the locking piece 11. The outer edge of the cast iron disc 15 has the same curvature as the inner edge of the locking piece 11. The center of the cast iron disc 15 is movably connected with the threaded rod at one end of the threaded handle 12. The conical block 16 is arranged in the cavity of the locking piece 11 and is located at the bottom of the cast iron disc 15. The top end of the conical block 16 has the same curvature as the outer edge of the cast iron disc 15. The compression spring 17 is arranged between the conical block 16 and the cast iron disc 15. The steel ball 14 is pre-set in the spherical groove 13. The surface of the locking piece 11 is provided with an annular array of spherical grooves 13. The center axis of the spherical groove 13 is offset to one side of the conical block 16. Therefore, the space of the steel ball 14 extending outward from the surface of the locking piece 11 is limited and does not exceed one third of its own volume under the extrusion of the conical block 16. The top end of the threaded handle 12 is provided with an annular anti-skid protrusion. The threaded handle 12 can be rotated to generate threaded transmission with the locking piece 11. The threaded rod of the threaded handle 12 controls the cast iron disc 15 to rise and fall under the threaded transmission. The cast iron disc 15 is in sliding fit with the inner wall of the locking piece 11. The cast iron disc 15 affects the state of the compression spring 17 in the process of sliding. When the compression spring 17 is in the compressed state, the conical block 16 can be linked to move vertically synchronously. The inclined end of the outer surface of the conical block 16 and the inclined end of the bottom of the limiting groove 10 form a right angle wrap angle structure. The steel ball 14 rolls along the outer surface of the conical block 16. The structure of the conical block 16 which is wide at the top and narrow at the bottom continuously extrudes the steel ball 14 to extend outward in the spherical groove 13 when it is lowered until the extruded steel ball 14 is attached to the outermost inner wall of the spherical groove 13. At this time, the steel ball 14 is attached to the inclined surface of the bottom of the limiting groove 10. Therefore, the steel ball 14 is clamped at the angle difference between the limiting groove 10 and the conical block 16. Because the steel ball 14 extends outward by one third, the steel ball 14 forms a lever force with the limiting groove 10 and the conical block 16. The limiting groove 10 needs greater extrusion force to affect the movement of the steel ball 14. The steel ball 14 is blocked by the outer wall of the conical block 16. The position height of the conical block 16 is controlled by the compression spring 17 in the compressed state. The compression spring 17 provides the reset spring force of the conical block 16. The locking force is completely generated by the lever effect of the steel ball 14 and the inclined surface. Example 2
[0049] Reference Figure 2For the second embodiment of the application, which is different from the first embodiment, the frame body 1 of this embodiment is integrally formed, and the inside of the frame body 1 is a hollow structure, and the shape of the hollow part is matched with the shape of the honeycomb layer plate 4; The size of the honeycomb layer plate 4 is the total volume of the frame body 1, and the outer surface of the honeycomb layer plate 4 is composed of a plurality of regular hexagonal honeycomb arrays, and each independent honeycomb cell 5 is provided with the same volume structure, and the inside of the honeycomb cell 5 is provided with microcapsules 6 and water absorbing resin 7, the microcapsules 6 occupy 60% of the volume space of the honeycomb cell 5, the diameter of the microcapsules 6 is 80±10μm, and the microcapsules 6 form a nested structure, the initial volume of the water absorbing resin is ≤5%, and after swelling, it fills the remaining 40% of the space and extrudes the microcapsules, and the microcapsules 6 are filled with triethylene glycol dimethacrylate, which is a liquid filled in the cracks, and after oxidation, it gradually solidifies to form a repair structure; The honeycomb cell 5 is also provided with water absorbing resin 7, which is in a granular structure, and the water absorbing resin 7 is pre-set in front of the microcapsules 6. When cracks occur on the surface of the frame body 1, external water vapor penetrates between the honeycomb cell 5 and the frame body 1, and the water absorbing resin 7 absorbs water vapor and expands, expanding its own volume by hundreds of times or more. After the water absorbing resin 7 expands to form a hydrogel, the hydrogel is pressed by each other, and the material properties of the hydrogel cannot separate the water, so the expanded hydrogel fills the inside of the honeycomb cell 5. After the honeycomb cell 5 is filled, it will extrude the microcapsules 6, and after the microcapsules 6 are extruded, they will break, and the triethylene glycol dimethacrylate inside the microcapsules 6 will flow from the gap of the hydrogel to the gap of the frame body 1, and after oxidation, it will become a solid; The whole honeycomb layer plate 4 is composed of honeycomb cells 5, so each honeycomb cell 5 that is in contact with the frame body 1 is provided with a honeycomb cell 5 that can repair cracks, so it can cover the whole frame body 1.
[0050] Compared with embodiment 1, further, the frame body 1 is integrally formed, and the use scene of embodiment 1 is different, the frame body 1 of this embodiment cannot replace the internal honeycomb layer plate 4, and lacks a certain flexibility, but the sealing performance is significantly improved compared with embodiment 1, and the frame body 1 is suitable for more severe environments, such as immersion in water and high dust environment. When the frame body 1 is still nearly serviceable after forming cracks and repairing, the whole frame body 1 needs to be replaced, different environments can choose the corresponding frame body 1 formed in different ways, and the embodiment prolongs the service life by increasing the microcapsule filling density to 80%.
[0051] The rest of the structure is the same as that of embodiment 1.
[0052] Comparative example 1 Reference Figure 10 For the preparation method of the dicyclopentadiene material of the application, this embodiment is different from the first embodiment and includes the following steps: The raw material capsule core is prepared from dicyclopentadiene, the capsule wall is prepared from urea 10 g, formaldehyde solution 25 ml, and ammonium chloride 0.5 g, and the emulsifier is sodium dodecyl sulfate 1 g; S1, 100 g of dicyclopentadiene and 1 g of sodium dodecyl sulfate are added to 500 mL of deionized water, and high-speed shearing emulsification is performed at 40°C and 8000 rpm for 15 minutes to form an O / W emulsion (particle size 50-100 μm); S2, urea 10 g is adjusted to pH 8.0 with formaldehyde 25 mL and reacted at 70°C for 1 hour to obtain a transparent urea-formaldehyde resin prepolymer; S3, the prepolymer is added to the emulsion, stirred at 300 rpm, and 10% ammonium chloride solution is added dropwise, then the pH is adjusted to 2.5, and reacted at 55°C for 3 hours to form microcapsules; S4, first filter treatment, and deionized water washing 3 times, vacuum drying at 40°C for 24 hours, and then sieving treatment (75-105 μm) to obtain white powder microcapsules.
[0053] Dicyclopentadiene needs to undergo ring-opening polymerization (ROMP) under the action of a catalyst, but there is a lack of effective catalyst in the photovoltaic frame crack environment, which causes the polymerization reaction to be unable to trigger, and the repair material remains liquid and cannot be cured.
[0054] Comparative Example 2 Reference Figure 11 , the preparation method of the epoxy resin material of the present application, which is different from the first embodiment, comprises the following steps: The raw material capsule core is prepared from dicyclopentadiene, the capsule wall is prepared from urea 10 g, formaldehyde solution 25 ml, and ammonium chloride 0.5 g, and the emulsifier is sodium dodecyl sulfate 1 g; S1, 100 g of dicyclopentadiene and 1 g of sodium dodecyl sulfate are added to 500 mL of deionized water, and high-speed shearing emulsification is performed at 40°C and 8000 rpm for 15 minutes to form an O / W emulsion (particle size 50-100 μm); S2, the epoxy resin is mixed with the curing agent and added dropwise to the aqueous phase, and emulsified at a speed of 4000 rpm for 20 minutes to form a W / O / W multiple emulsion (particle size ~ 80 μm); S3, the multiple emulsion is slowly stirred at a speed of 300 rpm for 1 hour after cooling to 10°C, and then 5 mL of glutaraldehyde is added dropwise and cross-linked and cured for 2 hours; S4, centrifugal separation, cold water washing, freeze-drying for 48 hours, and then sieving (75-105 μm) to obtain light yellow microcapsules.
[0055] Epoxy resin needs to rely on amine curing agent to trigger cross-linking reaction above 60°C, and the reaction rate at room temperature is very low (> 2 hours), which causes crack filling delay.
[0056] The steps of Comparative Example 1, Comparative Example 2 and Example 1 are implemented as shown in the following comparison table in combination with the drawings: Repair effect comparison: Test index Comparative Example 1 (DCPD) Comparative Example 2 (EPOX) Example 1 (TEGDMA) Crack filling rate ≤18% 42% 95% Water absorption reduction rate 8% 22% 92% Insulation resistance recovery rate <30% 65% >98% Key process control point comparison: Parameter Comparative Example 1 (DCPD) Comparative Example 2 (Epoxy) Example 1 (TEGDMA) Reaction type In-situ polymerization Complex coacervation Interfacial polymerization Temperature control 55±2℃ 10°C low temperature gel 60±1℃ pH adjustment 2.5 (acidic curing) 4.5 (isoelectric point) No adjustment needed Drying method 40°C hot air drying Freeze drying 35°C vacuum drying Particle size control method Emulsification shear rate Complex emulsification initial particle size Stirring speed adjustment It should be noted that the above examples are only used to illustrate the technical solutions of the present application and are not limiting. Although the present application has been described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present application can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application, and they should be covered in the scope of the claims of the present application.
Claims
1. A colorable, PID resistant, carbon fiber photovoltaic module frame, characterized by: The utility model relates to a kind of repair material injection device for concrete crack, including, Frame body (1), inside is equipped with openwork structure; Honeycomb layer board (4), embedded in the openwork structure of the frame body (1), the honeycomb layer board (4) is made of multiple regular hexagon honeycomb lattice (5) array; Microcapsule (6), filled in the honeycomb lattice (5) inside, its inside encapsulates the repair material of oxidizable curing; Water-absorbing resin (7), located in the honeycomb lattice (5) and in the front end of the microcapsule (6); The honeycomb lattice (5) is the tapered structure of front narrow and rear wide, for guiding repair material directional flow to crack area.
2. The colorable PID-resistant carbon fiber photovoltaic module frame according to claim 1, wherein: The frame body (1) is detachable structure and integral molding structure, and the frame body (1) detachable structure includes mutually symmetrical upper shell (2) and lower shell (3); The upper shell (2) and lower shell (3) are sealed by sealing silica gel (18) bonding.
3. The colorable PID-resistant carbon fiber photovoltaic module frame of claim 2, wherein: The outer side of the upper shell (2) and lower shell (3) is respectively equipped with locating block (8) and limiting block (9); The inner part of the locating block (8) and limiting block (9) is respectively provided with limiting groove (10).
4. The colorable PID-resistant carbon fiber photovoltaic module frame of claim 3, wherein: The limiting groove (10) is the circular cone structure of upper narrow and lower wide; Locking part (11) is movably inserted in the inner part of the limiting groove (10), for locking the vertical position of the locating block (8) and limiting block (9).
5. The colorable PID-resistant carbon fiber photovoltaic module frame of any of claim 4, wherein: The locking part (11) includes: Threaded handle (12), located at the top end of locking part (11); Cast iron disc (15), located in the cavity of locking part (11), and the threaded rod of threaded handle (12) is movably connected; Conical block (16), located below cast iron disc (15); Compression spring (17), located between cast iron disc (15) and conical block (16); Steel ball (14), located in the spherical groove (13) on the surface of locking part (11), is partially exposed by being extruded by conical block (16).
6. The colorable PID-resistant carbon fiber photovoltaic module frame of claim 5, wherein: The inclined end of the outer surface of the conical block (16) and the inclined end of the bottom of the limiting groove (10) form a right angle wrap angle structure; The steel ball (14) forms lever force lock when being pressed down by the conical block (16) and the bottom of the limiting groove (10).
7. The colorable PID resistant carbon fiber photovoltaic module frame of claim 2, wherein: The frame body (1) is integral molding structure, and the shape of the hollow part in the frame body (1) is completely matched with the honeycomb layer board (4).
8. The colorable PID-resistant carbon fiber photovoltaic module frame according to any one of claims 1-6, wherein: The water-absorbing resin (7) is granular, expands to form hydrogel when meeting water vapor, extrudes the microcapsule (6) and breaks to release repair material.
9. The colorable PID-resistant carbon fiber photovoltaic module frame of claim 8, wherein: The wall material of the microcapsule (6) is polyurethane, and the core material includes oxidized curing type repair monomer and initiator.
10. The pigmented PID-resistant carbon fiber photovoltaic module frame of claim 1, wherein: The tapered front end of the honeycomb lattice (5) is towards the inner wall surface of the frame body (1), and the rear end is towards the central axis of the honeycomb layer board (4).
Citation Information
Patent Citations
Anti-PID-effect photovoltaic assembly
CN204155944U
Anti-PID photovoltaic module and photovoltaic equipment
CN208820732U
Dye-sensitized solar cell and its manufacturing method
JP2005019132A
Solar cell module and seal material
JP2016208616A
Jump rope head with a jump rope self-locking function
JP3216889U
Cited By
Photovoltaic panel mounting structure of photovoltaic energy storage system
CN122316199A